2019
DOI: 10.4025/actascitechnol.v41i1.35571
|View full text |Cite
|
Sign up to set email alerts
|

Purification of phenolic compounds from genipap (<i>Genipa americana</i> L.) extract by the ultrasound assisted ultrafiltration process

Abstract: The aim of this study was to evaluate the potential of an integrated membrane process for purification of polyphenol and genipin components from genipap fruit extract. Optimal conditions for aqueous extraction of polyphenols from genipap fruit pulp were at 71°C for 49 min using a fruit pulp:water ratio of 1:3 (w w -1 ). Microfiltration with membranes of different pore sizes (0.22, 0.3 and 0.8 μm) resulted in a clarified permeate with similar physical-chemical properties, but the permeate flux through the 0.8 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Madrona et al. (2018) showed that the clarification of genipap extract through a 0.8 µm cellulose ester microfiltration membrane reduced TS and TSS contents of feed extract in 19.70% and 33.80%, respectively. The sequential process of centrifugation and membrane filtration was more effective than the single processes in clarifying the hibiscus extract, with a reduction of TS and TSS of 19.82 and 27.12%, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Madrona et al. (2018) showed that the clarification of genipap extract through a 0.8 µm cellulose ester microfiltration membrane reduced TS and TSS contents of feed extract in 19.70% and 33.80%, respectively. The sequential process of centrifugation and membrane filtration was more effective than the single processes in clarifying the hibiscus extract, with a reduction of TS and TSS of 19.82 and 27.12%, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Madrona et al. (2018) reported a permeate flux of genipap fruit extract through a flat polymeric membrane of 0.22 µm of 9.50 kg/m 2 hr –1 . Terra et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Madrona et al. (2019) used the ultrasound‐assisted ultrafiltration to purification of phenolic compounds from genipap extract. They concluded that application of ultrasound can increase the purity of permeate stream during ultrafiltration of genipap extract.…”
Section: Introductionmentioning
confidence: 99%